Tarzan - Collins, Phil.; Lima, Kevin; Buck, Chris; Burroughs, Edgar Rice, 1875-1950.; Driver, Minnie; Close, Glenn, 1947-; O'Donnell, Rosie; Walt Disney Pictures (Burbank, Calif. : Disney DVD : Distributed by Buena Vista Home Entertainment, 1999)
An orphaned human baby is raised by a family of gorillas and develops all the instincts and prowess of a jungle animal. But when the beautiful Jane makes an appearance in his jungle home, two very different worlds are about to become one.
Title from disc label.
Disc 1 includes the movie with French and Spanish language tracks; Descriptive TheatreVision for the visually impaired; Spanish subtitles; audio commentary featuring the producers and directors; Tarzan Read-Along (have the story read to you, or read the story by yourself); Tarzan Interactive Trivia Game; sneak peek at Disney's Dinosaur; Tarzan Action Game playable demo; Internet links to various Tarzan/Disney Websites.
Disc 2 includes The history and development of Tarzan; Introductions and explanations by the filmmakers; early presentation reel; the making of the music of Tarzan; original Phil Collins demos; Phil Collins music videos; behind the scenes with the voice talent; original story treatment; storyboard to final film split-screen comparison; abandoned sequences; The Deep Canvas Project; Glen Keane on the animation of Tarzan; character designs and concept art; production progression demonstration; trailers and posters.
Songs by Phil Collins ; directed by Kevin Lima, Chris Buck ; score by Mark Mancina ; based on the story Tarzan of the apes by Edgar Rice Burroughs ; screenplay by Tab Murphy ...[et al.] ; produced by Bonnie Arnold.
Starring the voices of Minnie Driver, Glenn Close, and Rosie O'Donnell.
DVD; Dolby digital; stereo.
Keywords: Tarzan (Fictitious character); Video recordings; Feature films; Animated films